High β-sitosterol-D-glucoside content in sweet potato varieties and its anti-breast cancer potential through multiple metastasis-associated signals - Jinyin Zhang; Lu Huang; Xiang Tang; Miao Pan; Xiaoli Ye; Xuegang Li; Hang Ma (Food Science and Human Wellness)
β-Sitosterol-D-glucoside (β-SDG) is a phytosterol compound whose antitumor activity has been confirmed by previous studies. However, its suppression on breast cancer remains unclear. To that purpose, we isolated β-SDG from sweet potato and investigated the breast-cancer-inhibiting mechanism using proteomic analysis. The sweet potato species S6 with high β-SDG content were chosen form 36 species and β-SDG was isolated by HPLC. Afterwards, an in situ animal model of breast cancer was established, and β-SDG significantly reduced the tumor volume of MCF-7 xenograft mice. Proteomic analysis of tumor tissues revealed that 127 of these proteins were upregulated and 80 were downregulated. Gene ontology and network analysis showed that regulatory proteins were mainly associated with epithelial-mesenchymal transition (EMT), myogenesis, cholesterol homeostasis, oxidative phosphorylation and reactive oxygen pathways, while Vimentin, NDUF, VDAC1, PPP2CA and SNx9 were the most significant 5 node degree genes. Meanwhile, in vitro and in vivo results showed that the protein expression of PPP2CA and Vimentin, which are markers of EMT, were involved in breast cancer cell metastasis and could be reversed by β-SDG. This work highlights β-SDG as a bioactive compound in sweet potato and the potential therapeutic effect of β-SDG for the treatment of breast cancer by inhibiting metastasis.